2018
DOI: 10.6065/apem.2018.23.1.38
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between subclinical hypothyroidism and serum levels of uric acid and creatinine in children aged 2–14 years

Abstract: Purpose Hypothyroidism is a clinical syndrome that can lead to elevated levels of serum creatinine and uric acid by causing impaired renal function. Although many studies have been carried out on the relationship between overt hypothyroidism and renal function, few studies have been conducted on subclinical hypothyroidism and renal function, especially in pediatric patients. For this reason, we studied this issue in children, so as to provide a background for more useful research and future education.Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
6
2
Order By: Relevance
“…The significant (p < 0.05) decrease in TSH may suggest that oxidative stress might have occurred due to the intake of tartrazine and curcumin. Sayari et al (2018) reported heavy presence of ROS or free radicals on the follicular cells of the thyroid gland; whereas, T 3 and T 4 which are stored, could decrease TSH. The increase in T 3 Table 5.…”
Section: Thyroid Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant (p < 0.05) decrease in TSH may suggest that oxidative stress might have occurred due to the intake of tartrazine and curcumin. Sayari et al (2018) reported heavy presence of ROS or free radicals on the follicular cells of the thyroid gland; whereas, T 3 and T 4 which are stored, could decrease TSH. The increase in T 3 Table 5.…”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…The increased level of TSH cause hyper stimulation of the thyroid gland, thus resulting in high levels of T 3 and T 4 ; however, due to negative feedback mechanism, increased level of T 4 and T 3 stimulates reduced production of TSH from the pituitary (Sayari et al, 2018). Among female mice, ingestion of diets containing turmeric oleoresin (curcumin) was associated with an increased incidence of thyroid gland follicular cell hyperplasia (NTP, 1993); histopathological changes in thyroid gland have been recorded by Shakoor (2019) in the high tartrazine and curcumin treated groups.…”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…Both overtly hypothyroid and SHypo patients may have high serum urea and creatinine levels, and regular monitoring of renal function is suggested as the renal dysfunction in TD is often reversible [ 44 , 90 ]. Resolution of hypothyroidism is associated with significant reduction in serum creatinine levels [ 91 ].…”
Section: Pragmatic Thyrovigilancementioning
confidence: 99%
“…In some of the studies, serum uric acid levels failed to show any significant elevation, especially in the pediatric patients with subclinical hypothyroidism. In one such study, Sayari et al 12 found that children with subclinical hypothyroidism did not have significantly different serum uric acid levels (p>0.05), although serum creatinine levels were significantly elevated, signifying a decline in the clearance of this substance.…”
Section: Discussionmentioning
confidence: 99%